Treatment of 36 cases of thrombotic thrombocytopenic purpura - Suvajdžić-Vuković Nada D.; Pandurović Radmila; Rajić Zoran; Milošević Rajko; Bogdanović Andrija D.; Lazarević Vladimir; Elezović Ivo V.; Čolović Milica R.; Budišin Živko; Savić Nebojša S.; Vučelić Dragica; Vavić Nataša; et al. (Vojnosanitetski Pregled)
Thirty-six patients (pts.) with thrombotic thrombocytopenic purpura (TTP) were treated between May 1990 and May 2003. There were 31 women and 5 men; the average age was 37 years. Twenty-five cases were idiopathic and 11 secondary (3 infection - related, 5 occurred during pregnancy and 3 were drug - associated). The mean lag period between the first symptoms and the diagnosis was 8.5 days (in 14 pts. £ 5; in 22 > 5). On diagnosis neurological symptoms were present in 31, bleeding in 33, fever in 21 and renal impairment in 27 patients. The mean hemoglobin was 67.5 g/L, the mean platelet count was 10´109/L, and the mean reticulocytosis was 17%. The mean serum LDH was 1457 IU. Treatment included plasma exchange (PE) in 24 pts. and only plasma infusions in 12 pts. There were 24 complete responders (20 on PE) and 12 deaths (4 on PE); PE significantly improved survival (p<0.01). There were 5 treatment-related complications due to the infection and bleeding, 17 exacerbations and 4 relapses. The mean time delay before the onset of symptoms and the treatment initiation lasted for 9 days suggesting the poor disease recognition; the mean time delay from diagnosis to PE institution was 6 days, indicating postponed PE. The mean treatment duration in all patients was 18 days; the mean number of PE cycles needed for the platelet count stabilization was 9. Good prognostic indicators of survival were: the longer prodromal period (>5 days), the secondary form of TTP and the absence of coma at presentation. The use of PE significantly improved survival. TTP is a severe disorder requiring early recognition and diagnosis in general medical care facilities, which should lead to the timely treatment with PE.